Evaluation of aldosterone antagonist utilization in heart failure with reduced and preserved ejection fraction at an academic medical center - Bradley D; Nappi J (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Aldosterone antagonists (AA) have historically been underutilized despite evidence that they reduce morbidity, mortality, and readmission rates to the hospital when used appropriately. Objective: We sought to determine if AAs were being prescribed in accordance with the 2013 ACCF/AHA guidelines and if there was any benefit surrounding 30-day readmissions or 30-day mortality for patients taking AAs with heart failure with reduced ejection fraction (HFrEF) or heart failure with preserved ejection fraction (HFpEF). Methods: We performed a retrospective chart review of adult patients who were discharged between October 1, 2015 and February 1, 2016 with any ICD-10 code for heart failure to assess compliance with guideline directed medical therapy. At baseline, patients were stratified by HFpEF and HFrEF. Patients were excluded if they died during the admission, discharged with hospice care, received a heart transplant or ventricular assist device, if they were miscoded or left against medical advice. Descriptive statistics, and Chi Square were used to evaluate the data. Results: We reviewed 601 patient charts for eligibility in our study, and determined 438 met the criteria for inclusion. Ninety-seven patients (22%) received an AA. Within the HFrEF group, only 37% of patients who were eligible per 2013 ACCF/AHA guidelines, received an AA at time of discharge. Fourteen percent of HFpEF patients were discharged on an AA. We found a trend towards decreased rates of our 30-day outcomes in patients who took AAs in both the HFpEF and HFrEF groups. Conclusions: AAs were underutilized during the timeframe we evaluated, despite the evidence for their use.